DEPENDENCE OF CHANGES IN THE HYGIENIC CONDITION OF THE ORAL CAVITY AND PERIODONTIUM IN CHILDREN WITH MALIGNANT TUMORS ON THE DURATION OF POLYCHEMYTHERAPY AND QUANTITIES OF CYTOSTATIC DRUGS - Yu.V. Popelo (Український стоматологічний альманах)
It is known that the course of cancer and chemotherapy adversely affect the components of homeostasis of the oral cavity, which causes stomatotoxicity. However, scientific publications have not yet provided generalized results of research on the pathogenetic mechanisms of the dental pathology formation during chemotherapy, which constitutes the relevance of this publication.